2021
DOI: 10.1096/fj.202001883r
|View full text |Cite
|
Sign up to set email alerts
|

Myelination defects in the medial prefrontal cortex of Fkbp5 knockout mice

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Among them, KIF5C is a protein‐coding gene that belongs to Kinesin 1. Over the years, KIF5C has been studied primarily in the nervous system (Choi et al, 2021); it can maintain the function of motor neurons and promote peripheral migration of the ganglion (DuRaine et al, 2018; Kanai et al, 2000). Studies have shown that KIF5C mutations are associated with cerebral cortical malformations and neurodevelopmental disorders, manifested as epileptic seizures in infants, neurobehavioral problems, including speech/language development deficits and a unique spectrum of brain malformations (Michels et al, 2017; Poirier et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, KIF5C is a protein‐coding gene that belongs to Kinesin 1. Over the years, KIF5C has been studied primarily in the nervous system (Choi et al, 2021); it can maintain the function of motor neurons and promote peripheral migration of the ganglion (DuRaine et al, 2018; Kanai et al, 2000). Studies have shown that KIF5C mutations are associated with cerebral cortical malformations and neurodevelopmental disorders, manifested as epileptic seizures in infants, neurobehavioral problems, including speech/language development deficits and a unique spectrum of brain malformations (Michels et al, 2017; Poirier et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Fkbp5 , encoding for FK506-binding protein 5, was another strongly induced transcript in oligodendrocytes at 7 dpi. It has previously been shown to be induced by glucocorticoids ( Hähle et al, 2019 ) and involved in myelination in the prefrontal cortex ( Choi et al, 2021 ). One of the main functions of oligodendrocytes is myelin formation around neuronal axons and the metabolic support of these to ensure neuronal signalling and information processing ( Lee et al, 2012 ; Moore et al, 2020 ; Saab et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that FKBP5 may be a candidate gene for human PTSD treatment. FKBP5 regulates hypothalamic-pituitary-adrenal axis (HPA) activity and regulates stressful stimuli (Choi et al, 2021 ). When subjects encounter threatening cues or stressful triggers, the HPA axis is activated, and the adrenal glands release glucocorticoids (e.g., cortisol in humans or corticosterone in rodents).…”
Section: Neurobiological Mechanisms Of Fear Extinctionmentioning
confidence: 99%